STRUKTUR DAN FUNGSI WACANA DALAM IKLAN BERBAHASA JERMAN : PENDEKATAN ANALISIS WACANA KRITIS - Herlina Jasa Putri Harahap; Regina Amelia; Gracia Togatorop; Nurhafiza Yusro; Nadia Sun Jayani Sagala (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This study analyzes the structure and function of discourse in German-language advertisements using a Critical Discourse Analysis (CDA) approach. The research aims to identify how linguistic elements and persuasive strategies are employed to construct meaning and influence the audience. A qualitative method is applied, utilizing textual analysis based on Fairclough’s model, which includes textual analysis, discourse practice, and social practice. The findings reveal that German-language advertisements not only rely on linguistic aspects but also reflect specific ideologies that shape consumer perceptions. The discourse structure in these advertisements employs persuasive strategies such as metaphor, euphemism, and intertextuality to enhance product appeal and establish a connection with the target market.